Compound Motor Action Potentials During a Modest Nerve Crush - Hamad, Mohammed Nazmy; Boroda, Nickolas; Echenique, Diego Barragan; Dieter, Raymond A.; Amirouche, Farid M. L.; Gonzalez, Mark H.; Kerns, James M. (Frontiers in Cellular Neuroscience, 2022)
Nerve crush injury results in axonotmesis, characterized by disruption of axons and their myelin sheaths with relative sparing of the nerve’s connective tissue. Despite the widespread use of crush injury models, no standardized method for producing these lesions has been established. We characterize a crush model in which a narrow forceps is used to induce a modest and controlled compressive injury. The instantaneous compound motor action potential (CMAP) is monitored in situ and in real-time, allowing the characterization of neuromuscular response during and after injury. The tibial nerves of 11 anesthetized rats were surgically isolated. After the placement of electrodes, CMAPs were elicited and registered using a modular-data-acquisition system. Dumont-#5 micro-forceps were instrumented with a force transducer allowing force measurement via a digital sensor. Baseline CMAPs were recorded prior to crush and continued for the duration of the experiment. Nerve crushing commenced by gradually increasing the force applied to the forceps. At a target decrease in CMAP amplitude of 70%–90%, crushing was halted. CMAPs were continually recorded for 5–20 min after the termination of the crushing event. Nerves were then fixed for histological assessment. The following post-crush mean values from 19 trials were reported: peak CMAP amplitude decreased by 81.6% from baseline, duration of crush was 17 sec, rate of applied force was 0.03 N/sec, and maximal applied force was 0.5 N. A variety of agonal phenomena were evident post-lesion. Following the initial decrease in CMAP, 8 of 19 trials demonstrated a partial and transient recovery, followed by a further decline. Thirteen trials exhibited a CMAP amplitude near zero at the end of the recording. Twelve trials demonstrated a superimposed EMG background response during and after the crush event, with disappearance occurring within 4–8 min. Qualitative histology assessment at the lesion site demonstrated a correspondence between CMAP response and partial sparing of nerve fibers. By using a targeted decline in CMAP amplitude as the endpoint, researchers may be able to produce controlled, brief, and reproducible crush injuries. This model can also be used to test interventions aimed at enhancing subsequent regeneration and behavioral recovery.